Population Dynamics of Sugarcane Moth Borers in Indonesian Cane Fields - Nader Sallam; Etik Mar'ati Achadian; Ari Kristini; Rob Magarey; Emily Deomano (Indonesian Sugar Research Journal, 2021)
We conducted monthly monitoring of lepidopterous moth borers in four sugarcane fields in Java, Indonesia, from May 2009 to May 2011. Fields sampled belonged to Pesantren Baru, Jombang Baru, Gondang Baru and Subang sugar factories. Three main moth borer species were found to inflict damage to sugarcane plantations in all regions, and these are the stalk borers Chilo sacchariphagus (Bojer) and Chilo auricilius Dudgeon and the top borer Scirpophaga excerptalis (Walker). Tetramoera (Eucosma) schistaceana (Snellen) was also encountered but only caused minor damage. Borer populations increased with plant age and reached a peak around January – May in most cases, with the onset of rainfall triggering population rise. All borers coexisted in the same plant with no evidence of competition between the two stalk borers (C. sacchariphagus and C. auricilius) over their specific feeding location (internode) or between the two stalk borers and the top borer (S. excerptalis) over the same plant. This suggests that an infestation by one species does not make the plant less desirable to be colonised by another. Parasitism rates by natural enemies were very low which reflects the challenges facing biological control efforts in Java. Knowledge generated through this project will improve our understanding of borer dynamics in South East Asia and will enhance our preparedness for potential introduction by any of these pests into Australia